Issues of ownership and access in the work of John Muir, John Buchan and Andrew Greig - Gifford, Terry (Revista Leitura, 2019)
This essay discusses two novels by two writers from Scotland: John Macnab, by John Buchan (1926) and The Return of John Macnab, by Andrew Greig (1996). These novels are examined through the lenses of ecocriticism havíng in mind a discussion of issues of ownership and access of the land. That Nature cannot be conceived except through the frames of culture is the main focus of the discussion. DOI: 10.28998/0103-6858.2005v2n36p23-34